Northwest history. Mining. Discovery. 1918-01-12 (1918)
Friend finds ore body - follows it 80 feet by drift on the lower level - The Friend Mining company has struck ore in the lower level of its property in the Beaver Creek district, Coeur d'Alene region, according to a report from William Schierding, president. "We have considerable shipping ore and intend to commence sorting by hand after February 1," he said.